Just a New Way to Roll - Lim, Si Wei (SARE: Southeast Asian Review of English, 2023)
Just a New Way to Roll follows the story of Hiroya, a Japanese college student on exchange in the United States of America in the mid-80s. There, he embarked on a journey to discover the true meaning of the authenticity in dishes created in ways other than what he was familiar with. Through his experiences with his new friend Dave, he realized that similar food items prepared differently elsewhere did not mean that they were not genuine; instead they were creative variations to suit the local preferences. Hiroya also learned that it was insensitive to judge each dish without ample knowledge of its origins, and what he thought he had grown up eating was in fact an adapted dish from another country. This story explores the subliminal ways of how food forms part of our identity, and how respecting the identity of others is as important as acknowledging our own.